Stewardship, Administration and Economic Sustenance for the Church: Towards a European Stewardship? - MIÑAMBRES, JESÚS (Prawo Kanoniczne, 2014)
Baptism brings with it the sharing of the vision and the mission of the Church, the stewardship that springs from conversion. The knowledge of this basic theological reality manifests itself in the commitment to provide for the needs of the community. The Catholic Conference of US bishops specificied the economic facets of this commitment as giving time, talent and treasure. This vision could be tried in other communities outside of the Church (political communities) and could offer a new perspective for basing the need to finance religious confessions.